Eavesdropping on and emulating MIFARE Ultralight and Classic cards using software-defined radio - Giechaskiel, I (2015)
In this report, we describe a Software-Defined Radio (SDR) approach for eavesdropping on Near Field Communications (NFC) and Radio Frequency Identification (RFID) cards operating at 13.56 MHz. We show that GNU Radio and Python make a great platform for prototyping, while maintaining sufficient performance for passive attacks without extensive optimizations and using only modest processing power. We successfully eavesdrop on real MIFARE Ultralight and Classic 1K cards by capturing the raw radio waves with a home-made antenna. We recover the plaintext of both reader and tag fully by demodulating the incoming radio waves, parsing individual bits and error detection codes into packets, and then decrypting them when necessary. On the transmission side, we achieve full software emulation of the reader and of MIFARE Ultralight and Classic 1K cards (including encryption), and partial hardware emulation, where we correctly modulate the signal, but not within the strict timing limits of the protocol. Our transmissions can also be used to prevent legitimate communication by interfering with the intended reader or tag signals.